Utilizing the Style Under Stress™ tool within Crucial Conversations© methodology to stimulate veterinary students' reflective practice of communication behaviors during client interactions - Bagley, Rodney S.; Mindthoff, Amelia (Frontiers in Veterinary Science, 2026)
Introduction“Crucial” conversations occur commonly in the veterinary profession and students require exposure to, and training in, these difficult communication dynamics.MethodsTo introduce the concept of how people respond during perceived crucial, intense, or difficult communication dynamics, we asked first-semester veterinary students to complete a “Style Under Stress™” self-assessment offered by the Crucial Conversations© (Crucial Learning) educational platform. This tool is used in the training of the Crucial Conversations© model and provides important insight into how people may respond during crucial conversations. First-year veterinary students in the initial (fall) semester of their curriculum completed this assessment beginning in 2016 (Class of 2020) continuing annually through fall of 2024 (Class of 2028).ResultsResponses were compared between classes (years) to determine student style consistency between years. Most students were assigned a “Silence” style (examples including “withdrawing,” “masking,” or “avoiding”) and this was preserved throughout the different years.DiscussionThe feedback provided through the assessment is used as a component of medical communication training in developing competency during crucial communication encounters. Students learn about their individual defaults as well as how others may respond in similar crucial conversation situations.